European Union values in documents of youth organizations operating in Poland - Czech-Włodarczyk, Celina; Cuprjak, Magdalena (Kultura-Społeczeństwo-Edukacja, 2026)
The article aims to present the research results concerning European Union values in the documents of youth organisations operating in Poland, namely: AIESEC Poland, ATD Fourth World, Youth Initiatives Center Horizons, UNESCO Initiatives Centre, All-Polish Youth, and the National Radical Camp. A qualitative strategy, the secondary source search method, was applied. Atlas.Ti software was used for coding. All the available documents posted on the websites of the investigated organisations, including their statutes, rules and regulations, and reports and accounts covering activities and operations, as well as Facebook posts, were analysed. An analysis of the content of these documents was carried out within the “values/ideas” category and the subcategories: standards, problematisation, and aims of activities. Within the analysis, the values present in the documents were compared with those enshrined in Article 2 of the Treaty on European Union, which also mentions pluralism, tolerance, justice, solidarity, non-discrimination, and equality. The carried-out analysis reveals whether the values guaranteed by all the member states of the European Union also underpin the mainstay of the activities of the youth organisations operating in Poland. <strong style="box-sizing: border-box; font-weight: bolder; color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Korekta autora: W dniu 12.01.2026 w zdaniu na stronie 75: "The study results presented hereunder are part of broader research carried out with-in the “anonymise” project" została wprowadzona zmiana polegająca na usunięciu słowa "anonymise" i wstawieniu po słowie "project" pełnej nazwy i numeru projektu: Heterotopias of Citizenship Educational Discourse and Pedagogies of Militarization in the Spaces of Youth Organizations. A Critical-Analytical and Comparative Approach, grant OPUS 18, no. 2019/35/B/HS6/01365, financed by Polish National Science Center.